Analysis of ESG Disclosure in ASEAN Countries: The Influence of Board CSR Orientation, Board CSR Strategy,GRI and National Cultural Demensions - Juanza Putri, Ledhisya; Fajri Andrianto; Masyhuri Hamidi (Dinasti Review, 2025)
This study aims to examine the influence of board CSR orientation, board CSR strategy, the adoption of the Global Reporting Initiative (GRI), and national cultural dimensions on Environmental, Social, and Governance (ESG) disclosure in ASEAN countries. The data used in this research is derived from 147 companies over the 2014–2023 period, with a total of 1,470 observations. The data analysis technique applied in this study is Panel Data Regression using STATA 17. Board CSR orientation was found to have a significant positive influence on ESG disclosure, as boards committed to CSR are able to enhance transparency and the quality of ESG reporting, as well as build stakeholder trust. Board CSR strategy also significantly encourages the integration of CSR into corporate strategies, which improves transparency and supports long-term sustainability goals. Furthermore, the adoption of GRI guidelines shows a significant positive impact, helping companies produce structured and comparable reports, thus enhancing competitiveness and investor confidence. In the aspect of national culture, individualism has a significant positive influence on ESG disclosure, as such cultures tend to emphasize transparency and reputation. On the other hand, uncertainty avoidance has a significant negative effect, indicating that cultures with low levels of uncertainty avoidance prioritize flexibility over structured ESG reporting. Meanwhile, the femininity dimension shows a positive but not significant impact on ESG disclosure, which may be attributed to weak regulatory frameworks in ASEAN. Control variables such as firm age, board size, and board meeting frequency also influence ESG disclosure.